IFPRI-AUC Joint seminar presentation - Kamaly, Ahmed (2018)
As part of the IIFPRI Egypt Seminar in partnership with AUC Economics Department | "THE LAUNCH OF IFPRI’s GLOBAL FOOD POLICY REPORT: “Reaping the benefits and facing the challenges of globalization in Egypt"